The Effects of Thawing Method on Consumer Palatability Ratings of Beef Strip Loin Steaks - Stephanie L. Witberler; Lindsey K. Decker; Erin S. Beyer; Morgan D. Zumbaugh; Michael D. Chao; Jessie L. Vipham; Travis G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2024)
Objective:The objective of this study was to determine palatability differences in beef strip loin steaks among various U.S. Department of Agriculture approved thawing methods and those commonly utilized by consumers. Study Description:Paired Low Choice beef strip loins (n=15) were collected and fabricated into six sections, each section was fabricated into 1-in steaks and assigned one of six thawing methods including: countertop, cook from frozen, cold water, hot water, microwave, and refrigerator. Steaks were cooked to an internal peak temperature of 160°F and consumers were given samples which they evaluated for juiciness, tenderness, flavor liking, overall liking, attribute acceptability, and perceived level of quality. Samples were rated on a 100-point scale with 0 indicating dry, tough, or dislike extremely, and 100 indicating extremely juicy, extremely tender, or like extremely. Results:For beef demographic data, consumers reported that the most important beef palatability trait was flavor with 56.7% of consumers indicating it as the most important. Tenderness was rated as the most important by 33.3% of consumers. Additionally, consumers reported the trait they experienced the most variability with was tenderness. Results of consumer sensory evaluation indicated that there were no differences (P>0.05) among the six thaw methods for juiciness, tenderness, flavor, and overall liking. However, all treatments had an average rating of at least 57 for overall liking, indicating a high level of eating satisfaction. For all thaw methods, at least 82% of steaks were rated as overall acceptable. Additionally, for all thaw methods, consumers rated at least 79.1% of steaks acceptable for juiciness, tenderness, and flavor liking. Furthermore, thaw method did not have an impact (P>0.05) on the perceived level of quality of samples. The Bottom Line:Beef strip loin steak palatability was not impacted by thawing method, and therefore consumers should use whichever thawing method is most convenient, or best suits their needs.
Keywords: beef; palatability; thawing